Profile Physical Fitness Athlete of Slalom Number Water Ski - Fachrezzy, Fahmy; Hermawan, Iwan; Maslikah, Uzizatun; Nugroho, Haris; Sudarmanto, Eko (International Journal of Educational Research & Social Sciences, 2021)
The purpose of this study was to find out the physical fitness profile of water ski athletes in the DKI Jakarta slalom number. This type of research is quantitative using descriptive methods. This study was conducted in Lake Sunter Jakarta, with a sample number of 41 male athletes slalom number. The instruments used in this study used physical fitness tests from the American Association for Health, Physical Education and Recreation (AAHPER) tests for sons while data analysis used descriptive frequency analysis. The results showed that the physical fitness of water skiers slalom numbers in the category of good or by 70.73%. Thus it can be concluded that the physical fitness of water skiers in the category is well-reviewed from the strength and endurance of the muscles of the arms and shoulders; endurance of the abdominal muscles; agility; power limbs; running speed; endurance of the heart.